Positive Psychology and Positive Criminology: Similarities and Differences. (February 2023) - Elisha, Ety; Ronel, Natti
The purpose of this review is to highlight the similarities and differences between positive psychology and positive criminology—both relatively new concepts that represent an optimistic view of human beings and their ability to recover—while calling for a change of focus in the discourse and research of their respective fields. To this end, we first present a brief overview of each of these perspectives, along with findings of studies that confirm their assumptions, and then address their similarities and differences, with an emphasis on positive criminology which is our area of expertise. We conclude that both approaches seek to improve the quality of life and well-being of individuals, families, and communities through the development of human strengths and skills and the provision of social assistance.